Employment Challenges of the Youth in Kosovo: Array - Hasanaj, Petrit; Ahmetaj, Besmir; Tërstena, Arben (Acta Universitatis Danubius. Œconomica, 2020)
This research is of a great importancet because it provides insights for the government of Kosovo, businesses and universities to focus more on creating employment opportunities for students, and thus reduce the level of unemployment within the country. This research also high-lights the need to develop relevant skills required in the labor market so that graduates with their knowledge and skills meet market requirements. The main purpose of this research is to identify some employment barriers faced by young people in Kosovo, in order to have a review of the challenges of Kosovo’s youth and how to overcome them. In this assignment the survey method with evaluation strategy is used, whilst the approach of this assignments is deductive based on the empirical literature. Also, structural data (questionnaire) are used since this method is more effec-tive and helps to collect more reliable data and enables to achieve objectives of this research. Ko-sovo has the highest unemployment rate in Europe and faces many challenges in creating em-ployment opportunities for young people. Work experience has a direct impact on the selection process of future employees and as such the lack of work experience is a major obstacle for young people in Kosovo when applying for work. This research is the first of its kind that deals with the employment challenges of young people in Kosovo, during the application process and finding a job. Also, this research is focused on a developing economy and the findings are in line with the proposals.